Brand Image, Daya Tarik Konten dan Program Gratis Ongkos Kirim: Studi Kasus Pembelian Flicka Bags di TikTok Shop - Rahayu, Banafsyafa Rasyida; Karsono, Lorena (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2024)
This research aims to analyze the influence of brand image, content attractiveness and the free shipping program on interest in purchasing Flicka Bags bag products on the TikTok Shop. The research method used a quantitative approach and involved 100 respondents, namely women aged 15-35 years, who had TikTok, knew the Flicka brand, had seen Flicka Bags content on TikTok and had bought or owned bag products from Flicka bags. The research results show that the brand image variable has a calculated t value greater than the t table (5,000 > 1,660) and a sig value (0,000 < 0,05). Content attractiveness variable (3.536 > 1.600) and a sig value (0,001 < 0,05), free shipping program variable (5.739 > 1.660) and a sig value (0,000 < 0,05). So each variable has a significant influence on interest in buying Flicka Bags bag products at the TikTok Shop. The results of the F test show that the F table is greater than the calculated F (19,911 > 2.70) and the significance value is (0.000 < 0.05) so that the three variables, namely brand image, content attractiveness and the free shipping program simultaneously have an influence on purchase interest. Flicka Bags bag products on TikTok Shop